The effect of water nutrients on weevil herbivory and development on water hyacinth - Mukarugwiro, Jeanne d' Arc (My University, 2016)
Because water hyacinth growth is highly dependent on nutrient availability, growth of the weevil Neochetina eichhorniae, which feeds only on water hyacinth, is closely linked to the plants’ nutrient status. The aim of this research was to investigate whether the nutrient levels could influence the larval development and larval feeding on water hyacinth. To investigate this, water hyacinth plants were grown at three different nutrient concentrations (high (6 mg/l N; 0. 83 mg/l P), medium (2.8 mg/l N; 0.4 mg/l P) and low (0.7 mg/l N; 0.01 mg/l) chosen according to a range of nutrient conditions found in South African water bodies. Control plants, without larval inoculation and treatment plants, with two larvae per plant were used. Plant biomass and other plant growth parameters were measured every week. We predicted a higher larval feeding rate on plants grown at the low nutrient level and faster larval development and a higher larval survival rate at the higher nutrient levels.
A research report submitted to the Faculty of Science,University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science. 2015.
Keywords: Water hyacinth.; Beetles.; Nutrition.